2018
DOI: 10.1097/iop.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Patient-Reported Outcomes for Surgically Amenable Epiphora

Abstract: Several PROMs have been used in the recent literature to evaluate patients undergoing surgery to treat epiphora. Assessed against standard criteria, no PROM has proven to be both psychometrically robust and clinically meaningful for use in this population. Future PROM development should be guided by this standard framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…[ 8 ] GBI is not procedure-specific and therefore also permits comparison across different in terventions, and can differentiate between successful and unsuccessful procedures. [ 9 ] Other methods of measuring QOL are Single-item symptom scores, single-item reports of improvement, Lacrimal Symptom Questionnaire (0.5%), Nasolacrimal Duct Obstruction Symptom Score, Ocular Surface Disease Index, Visual Function Questionnaire, the Short Form-36 Health Survey[ 10 ] and Lac-Q questionnaire[ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] GBI is not procedure-specific and therefore also permits comparison across different in terventions, and can differentiate between successful and unsuccessful procedures. [ 9 ] Other methods of measuring QOL are Single-item symptom scores, single-item reports of improvement, Lacrimal Symptom Questionnaire (0.5%), Nasolacrimal Duct Obstruction Symptom Score, Ocular Surface Disease Index, Visual Function Questionnaire, the Short Form-36 Health Survey[ 10 ] and Lac-Q questionnaire[ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of PROMs for surgically amenable epiphora identified that 69% of 227 studies included a PROM as the primary outcome measure, although in 48% the PROM was a single-item symptom score 80. The authors critically appraised each PROM and concluded that they lacked adequate content validity.…”
Section: Impact Of Proms By Ophthalmic Subspecialtymentioning
confidence: 99%
“…While in some, the epiphora represents no more than a tolerable nuisance, in others it significantly affects their quality of life. 4 At the more severe end of the spectrum, some cases necessitate repeated medical or surgical intervention for recurrent infection.…”
Section: Introductionmentioning
confidence: 99%